Apomorphine-induced reorganization of striato-frontal connectivity in patients with tremor-dominant Parkinson's disease. (October 2019) - Nigro, Salvatore; Bordier, Cécile; Cerasa, Antonio; Nisticò, Rita; Olivadese, Giuseppe; Vescio, Basilio; Bianco, Maria Giovanna; Fiorillo, Antonino; Barbagallo, Gaetano; Crasà, Marianna; Quattrone, Andrea; Morelli, Maurizio; et al.
Abstract: Introduction: Apomorphine is a dopamine agonist used in Parkinson's disease (PD), which matches levodopa in terms of the magnitude of effect on the cardinal motor features, such as tremor and bradykinesia. The beneficial effect of this treatment on PD patients with tremor-dominant has widely been demonstrated, although the underlying neural correlates are unknown. We sought to examine the effects of apomorphine on topological characteristics of resting-state functional connectivity networks in tremor-dominant PD (tdPD) patients. Methods: Sixteen tdPD patients were examined using a combined electromyography-functional magnetic resonance imaging approach. Patients were scanned twice following either placebo (subcutaneous injection of 1 mL saline solution) or 1 mg of apomorphine injection. Graph analysis methods were employed to investigate the modular organization of functional connectivity networks before and after drug treatment. Results: After injection of apomorphine, evident reduction of tremor symptoms was mirrored by a significant increase in overall connectivity strength and reorganization of the modular structure of the basal ganglia and of the fronto-striatal module. Moreover, we found an increase in the centrality of motor and premotor regions. No differences were found between pre- and post-placebo sessions. Conclusion: These results provide new evidence about the effects of apomorphine at a large-scale neural network level showing that drug treatment modifies the brain functional organization of tdPD, increasing the overall resting-state functional connectivity strength, the segregation of striato-frontal regions and the integrative role of motor areas. Highlights: We evaluate the neuronal effect of apomorphine in tremor-dominant PD. Apomorphine induces evident reduction of tremor symptoms. Apomorphine increases the overall resting-state functional connectivity strength. Apomorphine induces modular reorganization of the basal ganglia.